2014
DOI: 10.1364/oe.22.017735
|View full text |Cite
|
Sign up to set email alerts
|

Pseudo-random binary sequence phase modulation for narrow linewidth, kilowatt, monolithic fiber amplifiers

Abstract: We report on pseudo random binary sequence (PRBS) phase modulation for narrow-linewidth, kilowatt-class, monolithic (all-fiber) amplifiers. Stimulated Brillouin scattering (SBS) threshold enhancement factors for different patterns of PRBS modulated fiber amplifiers were experimentally analyzed and agreed well with the theoretical predictions. We also examined seeding of the SBS process by phase modulated signals when the effective linewidth is on the same order as the Brillouin shift frequency. Here ~30% varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 117 publications
(59 citation statements)
references
References 12 publications
1
53
0
2
Order By: Relevance
“…A pseudo-random bit sequence generator and fiber-coupled LiNbO 3 electro-optic modulator were then used to broaden the effective linewidth of the seed. To further reduce SBS in high-power fiber amplifiers, we have theoretically and experimentally investigated PRBS phase modulation [3]. PRBS is a periodic, deterministic, pseudo random signal widely used in digital communications.…”
Section: Kilowatt Class Fiber Amplifiersmentioning
confidence: 99%
See 1 more Smart Citation
“…A pseudo-random bit sequence generator and fiber-coupled LiNbO 3 electro-optic modulator were then used to broaden the effective linewidth of the seed. To further reduce SBS in high-power fiber amplifiers, we have theoretically and experimentally investigated PRBS phase modulation [3]. PRBS is a periodic, deterministic, pseudo random signal widely used in digital communications.…”
Section: Kilowatt Class Fiber Amplifiersmentioning
confidence: 99%
“…In particular, external phase modulation has led to the development of narrow-linewidth kilowatt class Yb-doped fiber amplifiers; which are highly desirable for beam combining applications. Specifically, white noise (WNS) [1][2] and pseudo-random binary sequence (PRBS) [3] phase modulation have been the prevalent linewidth broadening schemes. Although the effective linewidth of the laser would no longer be single-frequency, beam combining of high-power fiber amplifiers modulated at the GHz level has been demonstrated for both spectral [4] and coherent beam combining [1][2] (CBC) architectures.…”
Section: Introductionmentioning
confidence: 99%
“…통상적으로 브릴루 앙 이득의 대역폭인 수십 MHz 수준보다 충분히 크고, 최종 결합 빔 품질의 저하가 심각하지 않은 GHz 수준에서 시드 광의 선폭을 결정한다 [59] . 시드 광의 선폭 증대는 [59,64,65] . 전자는 일반적인 백색 노이즈 광원(White Noise Source)을 인가하는 방식으로, 구현이 가장 용이하다 는 장점을 가지지만 [59,64] , 시드 신호의 선폭을 임의로 조정하 기 어려운 단점이 있다.…”
Section: 분광형 다중 빔 결합 기술unclassified
“…전자는 일반적인 백색 노이즈 광원(White Noise Source)을 인가하는 방식으로, 구현이 가장 용이하다 는 장점을 가지지만 [59,64] , 시드 신호의 선폭을 임의로 조정하 기 어려운 단점이 있다. 반면에 후자는 모조 랜덤 이진수 시 퀀스에 따른 디지털 신호를 인가하는 방식으로, 확장된 시드 신호의 스펙트럼이 안정적이고 경우에 따라 실시간으로 조정 가능하다는 장점을 가지는 반면 전자에 비해 상대적으로 구현 이 복잡하고, SBS 억제 효과가 다소 감소되는 단점을 갖는다 [65] . 최근에는 임의 함수 생성기(Arbitrary Function Generator) 를 이용해 최적화 알고리즘을 거쳐 시드 신호의 스펙트럼을 최대한 균등하게 다수의 스펙트럼으로 분배하는 방식이 제 안된 바 있는데 [66] , 이는 임의 함수 생성기의 성능에 크게 의 존한다는 제약성을 가지나, SBS 억제 효과가 극대화될 수 있어서 최근 많은 주목을 받고 있다.…”
Section: 분광형 다중 빔 결합 기술unclassified
“…When the laser linewidth is broadened to GHz level, the SBS threshold will be enhanced significantly and the power scaling is easier accordingly [1]. Most recently, A. Flores et al demonstrated a 1.17 kW GHz-level-linewidth fiber amplifier [5]. The polarization state of this laser is random.…”
Section: Introductionmentioning
confidence: 99%